Evolution of the Content of the Service Function of the Tax Authorities - L. I. Goncharenko; K. D. Krayushkin (Управленческие науки)
The subject of the study is the activities of the Federal Tax Service (FTS of Russia), which annually strives to fulfil the objectives of not only increasing tax revenues to the budgets of the budgetary system of Russia, but also to improve the quality level of its activities. The key tool for the fulfillment of this goal for more than a decade remains digital technologies, allowing primarily for the improvement of tax control. Aim and objectives of the study. The analysis of the evolution of the development of technologies of control activity of tax authorities has led to the conclusion that strategically the control activity of the Federal Tax Service of Russia is increasingly built on the changing significance of other functions of tax authorities, among which the tax authority highlighted the service function. The article considers the foundations of the origin of the service function of tax authorities, transformation processes and development prospects taking into account new tools of interaction between tax authorities and taxpayers. At the same time, it touches upon the new services of the Federal Tax Service of Russia, as well as current directions of solving acute issues, in particular, the transition to EDI, the expansion of tax monitoring subjects, construction of a digital tax code, new tools for pre-trial consideration of tax disputes and minimization of tax risks. The study ultimately resulted in the construction of a scheme of the digital outline of the Russian tax system with the allocation of promising areas for further development.